Long-Term Administration of Anthraquinone Rhein on Induction of Constipation in Sprague-Dawley Rats via SCF/c-Kit Signaling Pathways - Bo Zhang; Mingdong Huo; Zhicheng Chen; Feng Gao; Yan Liu; Xingxin Zhou (Canadian Journal of Gastroenterology and Hepatology)
Background and Study Aims. It has been shown that abuse of laxatives is becoming a serious problem; therefore, a comprehensive understanding of its effect and possible mechanism on colon motility is essential to select effective treatments and avoid their abuse. Herein, we aimed to investigate the long-term stimulation of rhein on induction of constipation in rats and its underlying mechanisms. Materials and Methods. After establishing rat models of constipation, the rats were randomly divided into two equal subgroups and administered daily with normal saline (model control group) or 10 ml/kg PEG4,000 (PEG-treated group). Simultaneously, normal Sprague-Dawley (SD) rats were administered with normal saline (normal group). Physiological and fecal parameters were calculated, and intestinal transmission function was evaluated. After scarification, colonic tissues were freshly prepared for histological localization detected by immunohistochemical analysis and for the expression of stem cell factor (SCF) and c-kit proteins determined by western blot assay. Results. Following the initiation of rhein-induced rat constipation, body weight was lost slightly, the first time of black stool discharge was obviously longer, and the fecal moisture and number of fecal pellets decreased distinctly as compared with normal group. A decreased expression of SCF and c-kit was detected in model control group in comparison with normal group. Notably, compared with model control group, neither the alterations of fecal parameters and intestinal transmission function were effectively restored, nor the expression of SCF and c-kit was markedly elevated after administration of PEG4,000 for 30 d. Conclusion. Long-term stimulation of rhein can develop the constipation via SCF/c-kit signaling pathway, yet the symptoms of constipation and colon power cannot be alleviated or restored by PEG4,000. Collectively, these findings strongly suggest that long-term use of anthraquinone laxatives should be avoided for clinical treatment of constipation.